Sliding down the slippery slope? Trends in the rules and country allocations of the eurosystem's PSPP and PEPP - Annika Havlik; Friedrich Heinemann (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2020)
The Eurosystem has become one of the crucial players in the market for euro area government bonds. After first substantive purchases through the Securities Market Programme (SMP) in 2010, the Eurosystem's involvement has reached a new breadth and magnitude with the establishment of the Public Sector Purchase Programme (PSPP) in 2015. On top of this, the ECB Council has set up the Pandemic Emergency Purchase Programme (PEPP) in March 2020 in order to stabilize the euro area economy in the crisis and to contain the rise of sovereign risk premia.This study analyzes trends in the rules, volumes and country allocations of the two active sovereign purchase programmes, the PSPP and the PEPP. For an economic assessment, it is of importance to which extent the purchase programmes are of an asymmetric nature and whether the Eurosystem increasingly accepts the role of a strategic creditor who has veto power in debt negotiations.
Additional information: Study with support from the Brigitte Strube Foundation.
Keywords: 330; Euromarkt; Stabilisierungspolitik; Coronavirus; Europäische Finanzpolitik